Distribution of soil aggregates and associated organic carbon in relation to different types of land uses and depths - Barrales-Brito, Edgar; Paz-Pellat, Fernando; Velázquez-Rodríguez, Alma S.; Hidalgo-Moreno, Claudia; Etchevers-Barra, Jorge D. (REVISTA TERRA LATINOAMERICANA, 2021)
The aggregates distribution (masses) in different land uses and depths allows characterizing their structural stability and understanding the changes in the dynamics of carbon and mass distribution depending on the aggregates size. To model the distribution and mass of aggregates related to depth for different land uses, seven land uses were analyzed: Abies forest (BAr), Cupressus forest (BCr), Quercus forest (BQr), Abies forest with forest f ire (BAq), Quercus secondary forest (Bs), grassland (Pz) and agriculture with traditional tillage (Agt), all located on Mount Tlaloc in Texcoco, State of Mexico. Additionally, a conservation agriculture site (Agc) was selected in the lower part of Mount Tlaloc. To develop a general model, we started from the analysis of the patterns of the distribution of the accumulated mass (M acum) and accumulated carbon (C acum) in relation to the size of the aggregates, for different soil depths in each land use. Based on the adjusted mathematical models, a general model of n order kinetics was proposed as a cause for the observed solutions. The statistical adjustments were excellent (R2 > 0.99, generally).